Knowledge, skills and attitude towards reading English technical materials among students in selected technical secondary schools in Perak (IR) - Muhammad Putra Adha (2016)
This study was aimed to determine the status of reading knowledge, reading skills, reading purpose, reading interest and reading preference toward English technical materials among students in selected technical schools in Perak. The study was also intended to measure correlations between these variables and its significant differences based on selected demographics of students. The samples consisted of 120 students selected by simple random sampling from four schools. The instruments used were questionnaires and reading comprehension test. Statistical Package for Social Science version 20 was used to analyze data to obtain frequencies, percentages, means, standard deviations, t tests, Anova and Pearson correlations. The findings showed that the levels of reading skills, reading purpose were found to be high while their reading knowledge, reading interest and reading preference as they perceived were moderate. This study also revealed that male students obtained significantly higher mean scores in reading skills, reading purpose, reading interest and reading preference than their female counterparts. It was also reported that respondents who used mixed spoken languages at home obtained significantly higher mean scores in reading purpose, reading interest and reading preference. However, these three variables did not show significant differences among students whose parents come from different educational background and place of residence of parents. This study also indicated positive and moderate relationships existed among four reading abilities; reading skills, reading purpose, reading interest and reading preference. The findings of this study concluded that students' responses toward reading abilities reflected variability, and also, reading abilities among students in technical schools were still inadequate, particularly among female students and those from parents who only used mother tongue at home. Thus, this study recommends that greater efforts should be geared toward skills-upgrading courses in English language; developing innovative teaching methods and instructional materials as well as better access to quality reading English technical materials for technical and vocational instructors.